The Influence of Health Services Licenses to the Quality of Services at the Capital Investment and Integrated Services Office One Door of the City of Medan - Rosliana Rosliana; Juliandi Harahap; Achmad Rifai; Lucia Lastiur (Newinera Publisher, 2021)
The research objective was to analyze the effect of health service licensing policies on service quality at the Medan City Investment Service and One Stop Integrated Services. This research method is mixed methods, amounting to 27 people. The results of the research on the relationship of health service licensing policies with the satisfaction of the online licensing application for the SiCantik Cloud application, it is known that the licensing policy is good quality service with the relationship between physical evidence and satisfaction of the online licensing applicant for the SiCantik Cloud application, it is known that physical evidence of the applicant is satisfied, the relationship of reliability with the satisfaction of the online licensing applicant of the SiCantik application. Cloud, it is known the reliability of the applicant's clinical licensing officer, the relationship of responsiveness with the satisfaction of the online licensing applicant of the SiCantik Cloud application, it is known the responsiveness of the applicant's clinic licensing officer, the guarantee relationship with the satisfaction of the online licensing applicant for the SiCantik Cloud application, it is known that the clinical licensing guarantee of the applicant is satisfied, the relationship of empathy with the satisfaction of the licensing applicant online application SiCantik Cloud, it is known that the empathy of the applicant's clinical licensing officer is satisfied. Research suggestions are expected to the next researchers to prioritize research related to public services, especially health, because health services have a very important role in people's lives.